2020
DOI: 10.1016/j.psychres.2020.113366
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of the COVID-2019 pandemic: Perceived stress and coping strategies among healthcare professionals

Abstract: Highlights During a sudden and unprecedented event, such as the current pandemic, healthcare workers may be inadequately prepared and supported to cope with stressors and this negatively affected working environment. For healthcare professionals, a positive attitude towards the stressful situation was the main protective factor, while female gender, seeking social support, avoidance strategies and working with COVIDCOVID-19 patients were risk factors. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
371
7
31

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 340 publications
(467 citation statements)
references
References 41 publications
58
371
7
31
Order By: Relevance
“…The total scores range from 0 to 40, with higher scores showing higher levels of perceived stress. In this study, the Cronbach's α was very good (α = 0.883), similar to that in previous studies that used this same tool [35,36].…”
Section: Perceived Stress Scalesupporting
confidence: 88%
“…The total scores range from 0 to 40, with higher scores showing higher levels of perceived stress. In this study, the Cronbach's α was very good (α = 0.883), similar to that in previous studies that used this same tool [35,36].…”
Section: Perceived Stress Scalesupporting
confidence: 88%
“…These results are consistent with other past and current studies on infection disease outbreak indicating that problem solving is an active coping strategy with a psychological impact on stress reduction [13,33,34,35]. Some research during the current coronavirus pandemic among Italian general population has shown that seeking social support was positively related to perceived stress [33], and that higher social support predicted higher levels of stress [34]. In this study, a negative correlation was found between seeking social support and stress levels, but not at the level of statistical signi cance.…”
Section: Discusionsupporting
confidence: 92%
“…In this regard, for PLOS ONE example, these results may offer guidelines for the support of healthcare professionals, who report significant levels of subjective distress [63], but also on people who ask for a psychological treatment because of the pandemic, such as individuals, families and workers [68]. Moreover, these findings provide a further piece in a growing theoretical panorama which supports the importance of life satisfaction, mature defense mechanisms and coping strategies [24,34,41,57], by demonstrating its role in promoting effective strategies functional in the maintenance of emotional well-being.…”
Section: Resultsmentioning
confidence: 66%